From Searching for Cultural Integrity to Symbolism of Temple Building and the Organic Picture of Reality - VOREL, Jan (Bohemistyka, 2021)
The article is focused mainly on aesthetic-philosophical constants of the work of art of Julius Zeyer. The author of the article tries to point out that Zeyer´s conception of art is tightly connected with artistic conceptions of the rising literary symbolistic generation: His aesthetic-philosophical system contains strong protest against rationalism, realism and naturalism in contemporary literature and underlines the way to subconscious roots of human existence; it turns away from rational understanding of the world and the mystical intuition of inner and organic life in modern literature. In the article the motifs of temple building and motifs of creating the organic picture of the world in Zeyer´s work of art are analysed. The article also contains main references to Zeyer´s work of art published by reputable names of the Czech and European literary criticism.